Learning Through Uncertainty: A Phenomenological Study of Older, Professional Men Coping with Involuntary Job Loss - Brian Hentz (Adult Education Research Conference, 2016)
This phenomenological study explores how older, professional men coped adaptively with involuntary job loss, following the global financial crisis of 2008. Participants demonstrated skillful engagement, Stoic wisdom, narrative openness, and rugged interdependence to learn through the uncertainties that accompanied this unanticipated life transition.
Keywords: Adaptive change; transitional learning; adult development; gerontology